Virome Identification and Characterization of Fusarium sacchari and F. andiyazi: Causative Agents of Pokkah Boeng Disease in Sugarcane - Yao, Ziting; Zou, Chengwu; Peng, Na; Zhu, Yu; Bao, Yixue; Zhou, Qiujuan; Wu, Qingfa; Chen, Baoshan; Zhang, Muqing (Frontiers in Microbiology, 2020)
Fusarium sacchari and Fusarium andiyazi are two devastating sugarcane pathogens that cause pokkah boeng disease (PBD) in China. RNA_Seq was conducted to identify mycoviruses in F. sacchari and F. andiyazi isolates collected from PBD symptom-showing sugarcane plants across China. Fifteen isolates with a normal, debilitated, or abnormal phenotype in colony morphology were screened out for the existence of dsRNA from 104 Fusarium isolates. By sequencing the mixed pool of dsRNA from these Fusarium isolates, a total of 26 contigs representing complete or partial genome sequences of ten mycoviruses and their strains were identified, including one virus belonging to Hypoviridae, two mitoviruses with seven strains belonging to Narnaviridae, one virus of Chrysoviridae, and one alphavirus-like virus. RT-PCR amplification with primers specific to individual mycoviruses revealed that mitoviruses were the most prevalent and the alphavirus-like virus and chrysovirus were the least prevalent. In terms of host preference, more mitoviruses were found in F. andiyazi than in F. sacchari. Fusarium sacchari hypovirus 1 with a 13.9 kb genome and a defective genome of 12.2 kb, shares 54% similarity at the amino acid level to the Wuhan insect virus 14, which is an unclassiﬁed hypovirus identiﬁed from insect meta-transcriptomics. The alphavirus-like virus, Fusarium sacchari alphavirus-like virus 1 (FsALV1), seemed to hold a distinct status amid fungal alphavirus-like viruses, with the highest similarity of 27% at the amino acid level to Sclerotium rolfsii alphavirus-like virus 3 and 29% to a hepevirus, Ferret hepatitis E virus. While six of the seven mitoviruses shared 72-94% similarities to known mitoviruses, Fusarium andiyazi mitovirus 2 was most similar to Alternaria brassicicola mitovirus with a similarity of only 49% between the two viruses. Transmission of FsALV1 and Fusarium sacchari chrysovirus 1 (FsCV1) from F. sacharri to F. commune was observed and the characterization of the four-segment dsRNA chrysovirus was performed with aid of electron microscopy and analysis of the encapsidated RNAs. These findings provide insight into the diversity and spectrum of mycoviruses in PBD pathogens and should be useful for exploring agents to control the disease.